Digital Tax Literacy terhadap Kepatuhan Wajib Pajak - Anak Agung Liska Diana Putri; I Nyoman Putra Yasa; Putu Yunartha Pradnyana Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the contribution of digital skills in taxation in influencing taxpayers' regulatory obedience intentions by applying the Technology Acceptance Model (TAM) as its conceptual basis. The context of the study is rooted in Indonesia's ongoing digital tax transformation, exemplified by e-filing and e-billing systems, which require taxpayers to develop sufficient digital competence. Digital tax literacy is not limited to technical proficiency but also encompasses an understanding of system benefits, trust in digital platforms, and positive attitudes toward electronic tax services. The main objective is to explain how digital literacy affects perceived usefulness (PU) and perceived ease of use (PEOU), which drawing upon to TAM are central factors shaping behavioral intention. A qualitative research design was employed using a literature study approach, with data collected from academic journals, books, tax regulations, and official reports. The descriptive analysis involved reviewing, comparing, and synthesizing findings from earlier studies. The results indicate that enhanced digital literacy improves PU by increasing efficiency, accuracy, and transparency, while also strengthening PEOU by lowering usage barriers and boosting user confidence. Together, these elements shape favorable perceptions of digital taxation that ultimately reinforce compliance intentions. However, the study also identifies several obstacles, such as unequal access to infrastructure, varying levels of digital competence, and limited outreach from tax authorities. In conclusion, digital tax literacy emerges as a crucial driver of compliance in the digital era. The findings underscore the need for tax authorities to invest in literacy initiatives, broaden infrastructure coverage, and intensify public education regarding digital taxation. Beyond that, enhancing collaboration between government, educational institutions, and private sectors can accelerate digital adoption among taxpayers. Future research is encouraged to employ empirical methods across diverse taxpayer groups, ensuring deeper insights and more practical contributions for taxation policy and digital governance.